Meta-analysis of the efficacy of Jingjin acupuncture therapy in the treatment of spastic cerebral palsy - Kang, Xingyu; Huang, Ying; Zheng, Yi; Zhang, Qian; Gong, Rui; Tan, Jinlang; Ma, Le; Chen, Siyu; Lv, Xueyan; Shi, Shuai (Frontiers in Neurology, 2024)
Meta-analysis of the efficacy of Jingjin acupuncture therapy in the treatment of spastic cerebral palsy